Pengaruh Gaya Kepemimpinan, Budaya Organisasi, dan Komunikasi Organisasi Terhadap Kepuasan Kerja Serta Dampak Terhadap Kinerja Karyawan Bank Danamon Simpan Pinjam Cluster - Topan Alparedi; Hariya Toni (Universitas Batanghari, 2021)
This research has several goals, first analyze and prove the influence of leadership styles on performance of employees. Second, analyze and prove the influence of organizational culture on performance of employees. Third, analyze and prove the influence of employees ' performance against organizational communication. Fourth, analyze and prove the influence of leadership styles towards job satisfaction. Fifth, analyze and prove the influence of organizational culture towards job satisfaction. Sixth, analyze and prove the influence of communication towards job satisfaction. Seventh, analyze and prove the influence of job satisfaction on performance of employees. Eighth, analyze and prove the influence of job satisfaction as a medition on the influence of leadership styles on performance of employees. Ninth, analyze and prove the influence of job satisfaction as a medition on the influence of organizational culture on performance. Tenth, analyze and prove the influence of job satisfaction as a medition on the effect of organizational communication on performance of employees. The research of this population are all employees of Bank Danamon Cluster padang, while being sampled is 110 people respondents searched for using the formula Yamane. types and data sources used are primary data by means of questionnaires, further spread the use of secondary data. For testing data analysis using structural eqution model (SEM) through the course of AMOS while for testing the influence of variable pemediasi used sobel test. In accordance with the hypothesis testing on the model structure found that leadership style has no effect on performance is significant. Second, the culture of the organization significant effect on performance. Third, the influential organization communication was found significantly to performance. Fourth, it was found that the leadership style of influential significantly to job satisfaction. Fifth, it was found that organizational culture effect significantly to job satisfaction. Sixth, it was found that the Organization's influential communication significantly to job satisfaction. seventh, it was found that job satisfaction the significant effect on performance. Eighth, job satisfaction as medition significant kepemimipinan style has no effect on performance. Ninth, job satisfaction as medition significant influential culture on performance and job satisfaction as the tenth, medition has no effect significant organizational communication on performance.